Cough and Throat Clearing: Atypical GERD Symptoms or Not GERD at All?. Issue 5 (May 2016) - Abdul-Hussein, Mustafa; Freeman, Janice; Castell, Donald O.
Abstract : Goals: To investigate the frequency of throat clearing (TC) and cough and how often each is associated with a positive symptom index (SI) for reflux. Background: Many patients referred to our esophageal laboratory for gastroesophageal reflux disease (GERD) evaluation have "atypical" or "extraesophageal" symptoms. Study: We reviewed ambulatory impedance-pH studies of 267 patients referred for evaluation of possible GERD symptoms from January 2012 to December 2013 to evaluate the frequency of cough, TC, and their association with an abnormal number of reflux episodes. Patients with <3 symptom events/24 hours were excluded. Additional analysis was done for those with ≥24 (excessive) symptoms of TC or cough/24 hours. Eighty percent of patients were tested on proton pump inhibitor therapy. SI for either or both symptoms was calculated. Results: A total of 112 of 267 patients (42%) reported both TC and cough on study day, 76/267 (28%) cough without TC and 79/267 (30%) TC without cough. Only 9/112 (8%) had a positive SI, versus 20/76 (26%) and 17/79 (22%) for cough ( P =0.0006) and TC ( P =0.007), respectively. A total of 136 of 267 patients (51%) reported 3 to 23 TC events/24 hours; 27/136 (20%) had a positive SI. Fifty-five of 267 (27%) had "excessive" TC. Only 7/55 (13%) had a positive SI ( P =0.24). A total of 142 of 267 patients (53%) reported 3 to 23 cough events/24 hours; 43/142 (30%) had a positive SI. Forty-six of 267 (17%) had "excessive" cough. Only 6/46 (13%) had a positive SI ( P =0.02). Analyses based on ON/OFF therapy, also showed same low rate of positive test and significantly higher number of reflux episodes in those with positive SI. Conclusions: Although cough and TC are often considered possible GERD symptoms, there is a low probability of objective association. This is even less likely if both symptoms are present. Those patients who reported "excessive" cough are less likely to have a positive SI.